Seleção de uma cultura microbiana camercial para indústria de laticínios com baixa pós-acidificação e aumento de viscosidade em leites fermentados - Barth, Andréia Ruppenthal (Universidade do Vale do Rio dos Sinos, 2014)
The traditional cultures of lactic acid bacteria used in the preparation of fermented milk post-acidify even at refrigeration temperature. A careful selection could reduce the impacts caused by failures in the cold chain and improve the sensory quality of products offered to the consumer market. Therefore, the aim of this study was to select appropriate microbial cultures for the dairy industry, and the main feature was sought low post acidification and viscosity increase of fermented milks. The three cultures currently used in the dairy industry and five new cultures for yogurt and fermented dairy drink products were evaluated. Fermentation time was checked for both cultures, when the after acidification from the product was maintained at a temperature of fermentation, addition of pH and viscosity during the shelf life, when the product was cooled at 10 and 15 º C before packaging. The results show low viscosity and high post acidification for two currently cultures used by the company, which were discontinued. Three new cultures showed satisfactory results for the proposed objective. It was concluded that the choice of the microbial culture interferes strongly in the post acidification and viscosity for the product fermented dairy drink and that interference is not as significant for the yogurt product. Through this study it was found that the shelf life of fermented milk could be increased from 45 to 60 days.
Keywords: Iogurte; Cultura microbiana; Pós-acidificação; Viscosidade; Yogurt; Microbial culture; After acidification; Viscosity; ACCNPQ::Ciências da Saúde::Nutrição